Identification of nitrite treated tuna fish meat via the determination of nitrous oxide by head space-gas chromatography/mass spectrometry [version 2; peer review: 2 approved] - Markus Niederer; Sandra Lang; Bernard Roux; Thomas Stebler; Christopher Hohl (F1000Research, 2019)
Tuna fish meat is an expensive and highly perishable sea food. Fresh meat has a bright red colour which soon turns into an unsightly brown during storage. To prolong the aspect of freshness, the red colour is stabilised or even enhanced e.g. with carbon monoxide or nitric oxide, the product of a nitrite / ascorbic acid treatment, which bind as a ligand to myoglobin. These procedures are illegal. Here we present a method for identifying tuna meat samples, which have undergone fraudulent wet salting with nitrite. The method uses headspace-gas chromatography/mass spectrometry (GC/MS) for the determination of nitrous oxide, which is formed as the final product of the two-step reduction nitrite (added agent) to nitric oxide (ligand) to nitrous oxide (target compound). Complex bound nitric oxide is set free with sulfuric acid, which also promotes the reduction to nitrous oxide. The method was validated using 15N labelled nitrite as well as treated and untreated reference fish samples. A survey of 13 samples taken from the Swiss market in 2019 showed that 45 % of all samples were illegally treated with nitrite.